Relativity Of Literary Translation And Its Relationship To The Cultural Frameworks Of The Original Text And Its Translator (مجلة الواحات للبحوث والدراسات, 2023)
Abstract:    The relativity of translation appears more and more clearly when it comes to literary text. This latter is governed by cultural frameworks and intellectual backgrounds which may not be common with the cultural and intellectual frameworks of its translator. The role of the translator requires finding an equivalent that carries all the characteristics and levels of the original text, including its cultural aspect. And this poses great challenges to the translator of the literary text as well as the quality of his translated achievement, and whether his intellectual orientations are covered by a kind of prejudice and lack of neutrality. On this basis, this study aims at studying an aspect of the challenges of translating literature between the two parties (the original-translator text), concerning cultural specificities and intellectual backgrounds and the impact of this on the translated achievement. Accordingly, the most important things that we touched upon in our study are relativity and susceptibility to translating texts, literary translation and cultural situation, the cultural aspect of a literary text, the cultural background of the translator, and the intention of the literary text and the interpretation of the translator.Keywords: literary translation, cultural frameworks, original text, translator